2022
DOI: 10.1080/2162402x.2022.2101596
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral gene signatures reveal distinct cancer patient immunotypes with therapeutic implications for autologous DC-based vaccines

Abstract: Dendritic cells (DCs) have received considerable attention as potential targets for the development of novel cancer immunotherapies. However, the clinical efficacy of DC-based vaccines remains suboptimal, largely reflecting local and systemic immunosuppression at baseline. An autologous DC-based vaccine (DCVAC) has recently been shown to improve progression-free survival and overall survival in randomized clinical trials enrolling patients with lung cancer (SLU01, NCT02470468) or ovarian carcinoma (SOV01, NCT0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…For example, 3 out of 146 patients with solid tumours receiving BLZ945 showed partial response [ 146 ]. Furthermore, additional analysis of peripheral blood monocytes did not show any changes after treatment [ 147 , 148 ].…”
Section: Immunotherapy Targeting Tamsmentioning
confidence: 99%
“…For example, 3 out of 146 patients with solid tumours receiving BLZ945 showed partial response [ 146 ]. Furthermore, additional analysis of peripheral blood monocytes did not show any changes after treatment [ 147 , 148 ].…”
Section: Immunotherapy Targeting Tamsmentioning
confidence: 99%
“…In another study further evaluating the potential prognostic markers for moDC vaccine response, the presence of Tregs in the blood was found to be a negative prognostic factor in OC patients. Indeed, only in patients with a low number of Tregs did the CD8 + T cells increase after moDC vaccination [ 98 ]. In addition, patients that had received moDC vaccination (both Arms 1 and 2) also showed the presence of antigen-specific cytotoxic T cells in the blood [ 97 ].…”
Section: Dcs Vaccines In Ocmentioning
confidence: 99%
“…In addition, current designs of therapeutic algorithms also rely on combinations of DC-based cancer vaccines with other therapeutic modalities [ 151 , 152 ]. There is also a developing new field that attempts to identify new biomarkers that could predict the therapeutic efficacy of the vaccines based on the patient’s immunotype [ 153 ].…”
Section: Dcs In Immunotherapy Of Solid Tumorsmentioning
confidence: 99%
“…Despite many disappointments in clinical trials, the use of these cells still showed a notable therapeutic efficacy, and their role in cancer immunotherapy is indeed still ongoing [ 146 , 154 , 155 ]. As research into immunotherapy accelerated after the immune checkpoint inhibitor had entered the field, the efficacy of DC-based immunotherapy was found to be largely restricted by the settings (immunotype) of the patient’s tumor immune microenvironment [ 153 , 156 ]. Moreover, there is growing evidence that the functional heterogeneity of DC populations is even more complex than previously thought [ 73 ], and, therefore, more attention needs to be paid to the way DCs are ex vivo produced for ACT [ 82 ].…”
Section: Mc/dc Interplay As the Cellular Immune Checkpoint For Cancer...mentioning
confidence: 99%